Optimization of hydrothermal liquefaction of palm kernel shell and consideration of supercritical carbon dioxide mediation effect - Chan, Y.H. (Elsevier B.V., 2018)
The production of bio-oil from palm kernel shell (PKS) via subcritical and supercritical hydrothermal liquefaction was investigated. In order to maximize the bio-oil yield, design of experiment and optimization was performed using Response Surface Methodology (RSM) with central composite rotatable design (CCRD). Four factors which included temperature (330â390 Â°C), pressure (25â35 MPa), reaction time (60â120 min) and biomass-to-water ratio (0.20-0.50 wt/wt) were investigated. The regression model developed gave accurate predictions and fitted well with the experimental results, with coefficient of determination R2 of 0.9109. Based on the model, the optimum liquefaction condition was predicted to be at temperature of 390 Â°C, pressure of 25 MPa, reaction time of 60 min and biomass-to-water ratio of 0.20 with a prediction yield of 15.48 wt. This condition was validated by experimental runs which produced an average of 14.44 wt bio-oil yield. Then, the mediation effect of supercritical CO2 on bio-oil yield was studied. Hydrothermal liquefaction of PKS was performed at the optimum condition in the presence of supercritical CO2. The effect of supercritical CO2 was found to be insignificant at higher liquefaction temperature of 390 Â°C but it was significant at lower liquefaction temperature of 300 Â°C, producing bio-oil yield of 11.35 wt. GC/MS analysis showed that phenolic compounds constituted the major portion of the bio-oils, while ketones, aromatic compounds and carboxylic acid were also detected. Â© 2017 Elsevier B.V.